Policies for distance teacher education in Brazil: The structuring factors of Distance Education and the Open University of Brazil (Research, Society and Development, 2021)
This paper discusses teacher training in Brazil through distance education, with the Open University of Brazil Program as its object of analysis. This is an excerpt from the 2019 doctoral thesis entitled: “the initial training of distance teachers in Brazil: the contours and trajectories of the Open University of Brazil System in the region of Triângulo Mineiro and Alto Paranaíba in the period from 2013 to 2018” . The research was supported by the dialectical historical materialism method, having as main sources the bibliographic research and the documentary analysis of documents from Capes, Ministry of Education, about the UAB Program. It was found that teacher training policies in Brazil were influenced by four central factors: international organizations, the neoliberal agenda, changes in the capitalist accumulation system and the advent of digital communication and information technologies, especially from the years 1990. In this scenario, legislation favorable to the introduction of distance education in the country and, subsequently, of the UAB, was created. Then there was a movement towards the privatist-mercantile training model with the participation of the private sector and the adoption by the State of the UAB Program as an important locus of teacher training in the country. It was noted that the State attributed to the UAB the need to adopt mechanisms to reduce costs and make work precarious, with the consequent massification of teacher training.